please pa help po please
![Please Pa Help Po Please class=](https://ph-static.z-dn.net/files/db5/93fbb4faf300a5d703110b83629327cf.jpg)
Answer:
1.2x(4x^2−5x+3)
(2x)(4x^2+−5x+3)
(2x)(4x2)+(2x)(−5x)+(2x)(3)
=8x^3 − 10x^2 + 6x
2.-5m^2n(3m^3n-4m^2n^4)
((−5m^2)(n))(3m^3n+−4m^2n^4)
((−5m^2)(n))(3m^3n)+((−5m^2)(n))(−4m^2n^4)
=−15m^5n^2 + 20m^4n^5
3.(3x−4)^2
(3x+−4)(3x+−4)
(3x)(3x)+(3x)(−4)+(−4)(3x)+(−4)(−4)
9x^2−12x−12x+16
=9x^2 − 24x +16
4.(x+7)(x+8)
(x+7)(x+8)
(x)(x)+(x)(8)+(7)(x)+(7)(8)
x2+8x+7x+56
=x^2 + 15x + 56
5.(2x−5)(3x−7)
(2x+−5)(3x+−7)
(2x)(3x)+(2x)(−7)+(−5)(3x)+(−5)(−7)
6x^2−14x−15x+35
=6x^2 −29x + 35
Step-by-step explanation:
You're Welcome, Also this ^ means its an exponent